Eco-Relational Khalifah: A Posthumanist Performative Critique on The Modern Qur’an Commentaries - Fakhri Afif; Rezza P. Setiawan (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
This paper critically examines the construction of modern subjectivity within Islamic discourse, particularly through modern Qur’anic commentaries, and its implications for understanding the concept of “khalīfah.” Modern interpretations often reinforce anthropocentric essentialism, Cartesian dualism, and individual metaphysics, which situate humans as dominators over nonhuman creation, separate the spiritual from the material, and isolate individuals from other subjects. Through an analysis of hermeneutical engagement of prominent modern Muslim exegetes on the Qur’anic concept of khalīfah, this study identifies patterns of anthropocentric essentialism, dualistic thinking, and individual metaphysics in modern understanding of khalīfah. The research then explores how these frameworks limit ecological and relational understandings of khalīfah. In response, this paper proposes a posthumanist and performative reimagining of khalīfah based on relational metaphysics by drawing on contemporary philosophical perspectives. This reinterpretation shifts from human-centered dominion toward a recognition of the dynamic intra-action between human and nonhuman agents, offering a more holistic and ethically responsible interpretation aligned with the Qur’anic vision of interconnected creation